TRANSLATION AND VALIDATION OF A SCALE TO ASSESS THE PHYSICAL EXAMINATION SKILLS OF BRAZILIAN NURSES - Endlich, Jéssica Alexandra Majevski; Mozer, Carla Aparecida do Nascimento; Santos, Lucyara Silvares dos; Furieri, Lorena Barros; Fioresi, Mirian (Cogitare Enfermagem, 2024)
Objective: To translate, adapt, and validate, for the Brazilian context, a scale for assessing physical examination skills and to measure the frequency of Brazilian nurses performing these skills. Method: A methodological study conducted between September 2021 and August 2022 in Vitória, Espírito Santo. A scale was translated and cross-culturally adapted according to Fortes CPDD and Araújo AP. The instrument was evaluated by judges, with content validity, and applied to nurses. Descriptive and inferential statistics were used to analyze the data. Results: The scale was translated, adapted, and validated, achieving semantic and conceptual equivalence (content validity index: 0.99 for clarity and 0.98 for relevance). When applied, 80% of the skills were performed frequently. Conclusion: After translation, adaptation, and validation, the instrument became viable for application in research related to Brazilian nursing, which can contribute to improving the care provided.